Genetics and autoantibodies (2013)
Autoimmune diseases (ADs) are chronic conditions initiated by the loss of immunological tolerance to self-antigens. The pathogenic hypothesis comprises a complex interaction between genetic, environmental and hormonal factors that interact with an individual over time generating a dysregulation of the immune system leading to disease development. Several polymorphic genes contribute to the development of ADs. Furthermore, age and gender play a major role by influencing hormone levels that can represent the fulcrum unbalancing from susceptibility to protection. Evidences suggest that while all these steps occur, the susceptible individual develops autoantibodies over a long time lapse. Such autoantibody production is genetically determined and finally, their presence seems to determine the clinical presentation of ADs. The genetic predisposition to the developments of autoantibodies and toward the disease process may overlap. The unveiling of these mechanisms could allow not only to treat but also to prevent the development of autoimmune diseases. © 2013 Springer Science+Business Media New York.